Analysis of Quality Sanitation Market In The Block C Market of Wonokromo City of Surabaya Year 2019 - Fitrianti Dwi Anggraeni, Annisa; Kanah Arieska, Permadina (PROCEEDING SURABAYA INTERNATIONAL HEALTH CONFERENCE 2019, 2020)
Sanitation of Public Places is organizing the effort being made to environmental health through supervision and improvement of the quality of the environment by the main target public places. The purpose of this research is to analyze the quality of the sanitary market in block C Market Wonokromo Surabaya Kepmenkes Number 519 based on the year 2008 on Guidelines Healthy Market of organizing. This research uses descriptive design research with qualitative approach. Informant research by as much as 15 people. Data collection covers the field observations, interviews, and documentation. Data analysis using the technique of triangulation method. Sanitary components market assessment include the provision of clean water drainage, bathrooms, hand-washing place, SPAL, waste management, where sales of food ingredients, disinfection, and animals penular disease. The results obtained from the research aspects of the provision of clean water (50.0%) have been met. Bathroom requirements have been met (54.5%). Aspects of drainage and SPAL there are three criteria are met (50.0%). Assessment of waste management there are four aspects of assessment indicators (57.1%) have been met. Component sales place foodstuffs meet the requirements (75.0%). Hand-washing place aspect has not been fulfilled (100.0%). Assessment of penular animal diseases there is one of the indicators are met (50.0%). There is one indicator of the disinfection component assessment are met (50.0%). Sanitation in block C of Surabaya Wonokromo Market status is good enough. Efforts are being made to improve sanitation include doing coordination and collaboration with interested parties and stakeholders related to the holding of a healthy market, reactivate the means of sanitation facilities that have not been are met, as well as the improvement of the management of waste management.